Systemic infection of plants by a gemycircularvirus (family Genomoviridae) - Mendes, Tales da Silva (2019)
The Genomoviridae family includes non-enveloped, ssDNA viruses with circular genomes ranging from 2 to 2.4 kb, containing two ORFs separated by an intergenic, non-coding region. One of the ORFs, located in the virion-sense strand, encodes the putative coat protein (CP), and the other, in the complementary-sense strand, encodes a putative replication-associated protein (Rep) similar to the Rep protein found in members of the family Geminiviridae. Currently, the Genomoviridae family contains 73 viral species classified into nine genera, with Gemycircularvirus as the largest genus. Members of the family have been identified in mammals, birds, invertebrates, in a variety of environmental samples, and also in plants. However, despite the large number of reports and their pervasive presence in the environment, the infectivity of genomovirids to specific hosts remains largely unknown. The gemycircularvirus SsHADV-1 remains the only genomovirid with a known (fungal) host. The genus Gemycircularvirus includes all plant-associated genomovirids found so far. It is possible that gemycircularviruses play relevant ecological roles in association with plants. Here, we report the first case of systemic infection of plants by a gemycircularvirus, Euphorbia heterophylla associated gemycircularvirus (EuaGmV). A dimeric clone (~4.4 kb) of EuaGmV was used for the biolistic inoculation of plants of Euphorbia heterophylla and Nicotiana benthamiana. Control plants (of both species) were inoculated with the geminivirus Euphorbia yellow mosaic virus (EuYMV) or with water. At 21 and 28 days after inoculation (dai), non-inoculated upper leaves of the EuaGmV-inoculated plants (which did not show any symptoms) were collected for PCR-based analysis of the presence of the virus. Eight plants of E. heterophylla and all 10 plants of N. benthamiana were PCR-positive for the presence of EuaGmV. Amplicons (612 bp) obtained from E. heterophylla were sequenced, and a 99.6% identity with the sequence of the EuaGmV clone was obtained. These results demonstrate, for the first time, that a gemycircularvirus (family Genomoviridae) is capable of systemically infecting plants.